Optimalisasi Hasil Belajar Kognitif Pecahan Biasa melalui Implementasi Alat Edukasi Manipulatif Puzzle Pecahan (Mapupec) - Azifah, Nur; Sutoyo, Sutoyo; Jalil, Muhamad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Problems identified at MI Islamiyah Syafiiyah include limited learning media, especially the use of simple theme books and accompanying books, which causes low cognitive learning outcomes. This research aims to evaluate the use of the Manipulative Fraction Puzzle (Mapupec) educational tool in increasing students' cognitive learning achievement. The research method applied is Classroom Action Research (PTK) by implementing the Kemmis and Mc model. Taggar in two rounds of the cycle. Each cycle involves four stages, namely planning, acting, observing, and reflecting. The research subjects consisted of 41 class IV students at MI Islamiyah Syafiiyah. Data was collected through test instruments, observation and documentation, with data analysis using a quantitative approach. The findings from the research indicate that the use of the Fraction Puzzle Manipulative educational tool (Mapupec) is able to improve the cognitive learning outcomes of class IV students at MI Islamiyah Syafiiyah. The evaluation value in cycle I showed an increase from 21.95% to 70.73%, while in cycle II, the results increased again to 85.37%. These findings conclude that the use of Fraction Puzzle Manipulative educational tools is not only a learning tool, but also an educational game that can stimulate the brain, hone the speed of thinking, and train coordination between the mind and hands.